Use of 3D problem visualization method in training - Bozorov E.X; Baymuratova I.V. (Utilitas Mathematica, 2025)
Objective: The utilization of three-dimensional problem visualization as a novel pedagogical approach to the instruction of medical informatics at the post-secondary level. Methods: Use of a new method of 3D problem visualization training on the basis of Google and Microsoft cloud platforms using InVersalius software Findings: A novel approach to pedagogical practice within the context of medical disciplines was devised, and the user interface of the InVersalius application was enhanced. The impact of the implementation of a three-dimensional visualization methodology on the quality of educational outcomes was evaluated. Novelty/improvement: This marks the inaugural instance of utilizing a three-dimensional problem visualization methodology founded upon InVesalius software, in conjunction with Google and Microsoft cloud platforms, within the context of medical education.